Curves with constant geodesic curvature in the Bolyai-Lobachevskian plane - GÁBOS, Zoltán; MESTER, Ágnes (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The aim of this note is to present the curves with constant geodesic curvature of the Bolyai-Lobachevskian hyperbolic plane. By using the Lobachevskian metric the equations of the circle, paracycloid and hipercycloid are given. Furthermore, we determine a new family of curves with constant curvature which was not emphasized before. During the analysis we use Cartesian and polar coordinates. Mathematics Subject Classification (2010): 53A35.